RESEARCH METHODS FOR ENGLISH STUDIES - GABRIELE GRIFFIN (EDINBURGH EDINBURGH UNIVERSITY PRESS, 2013)
With a revised Introduction and with all chapters revised to bring them completely up-to date, this new edition remains the leading guide to research methods for final-year undergraduates, postgraduates taking Masters degrees and PhDs students of 19 th - and 20 th -century Literary Studies.
Keywords: English Literature-Research Methdology